The Role of Non-Discrimination in a World of Discriminatory Preferential Trade Agreements - Kamal Saggi; Woan Foong Wong; Halis Murat Yildiz (Center for Economic Studies and ifo Institute (CESifo), 2020)
In a three-country model of endogenous trade agreements, we study the implications of the Most Favored Nation Clause (MFN) when countries are free to form discriminatory preferential trade agreements (PTAs). While PTA members discriminate against non-member countries, MFN requires non-members to treat PTA members in a non-discriminatory fashion. We show that MFN reduces the potency of a country's optimal tariffs and therefore its incentive for unilaterally opting out of trade liberalization. Thus, MFN can be a catalyst for trade liberalization. However, when PTAs take the form of customs unions, the efficiency case for MFN as well as its pro-liberalization effect is weaker since one country finds itself deliberately excluded by member countries as opposed to staying out voluntarily.
Keywords: F11; F12; 330; trade agreements; tariffs; customs unions; World Trade Organization; coalition proof Nash equilibrium; welfare